2018
DOI: 10.1177/1129729818803870
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical variants of upper arm veins on preoperative mapping venography for hemodialysis access in Korean adults

Abstract: This study was a single-center, retrospective analysis of patients who underwent preoperative vein mapping of access creation between June 2014 and June 2017. This study was approved by the institutional review board of the authors' institute, and informed consent was waived in view of its retrospective nature. All patients underwent venography prior to access placement if they had a history of central venous catheterization (CVC) or if they were unsure whether they had undergone past CVC. All patients were do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 10 publications
0
11
1
1
Order By: Relevance
“…It is known that veins in the cubital fossa are frequently used in clinical procedures such as venipuncture, transfusion, infusion, cardiac catheterization, and vascular access for dialysis, and these veins are significant in traditional diagnosis and treatment procedures [ 6 , 12 , 13 ]. The arteriovenous fistula (AVF) procedure is a common technique used to gain vascular access in patients with chronic renal failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that veins in the cubital fossa are frequently used in clinical procedures such as venipuncture, transfusion, infusion, cardiac catheterization, and vascular access for dialysis, and these veins are significant in traditional diagnosis and treatment procedures [ 6 , 12 , 13 ]. The arteriovenous fistula (AVF) procedure is a common technique used to gain vascular access in patients with chronic renal failure.…”
Section: Discussionmentioning
confidence: 99%
“…The arteriovenous fistula (AVF) procedure is a common technique used to gain vascular access in patients with chronic renal failure. In this method, a fistula is created between the CV or BV and the brachial artery [ 12 , 14 ]. Alamshah [ 14 ] reported that the rate of deterioration of venous drainage might be lower in an AVF procedure performed in a pattern where the connection between the deep veins in the forearm and MCV is observed.…”
Section: Discussionmentioning
confidence: 99%
“…The nature of the human body inspires from the dawn of mankind to the present day. Despite of new alternative methods the anatomical dissection still remains the golden standard in the study of structure of human body (3). Searching of new patterns or variations of structures of the human body are the most important challenge for every anatomist (6,8).…”
Section: Introductionmentioning
confidence: 99%
“…The deep system consists of veins accompanying the arteries, whose names come from the accompanying arteries. Usually, in this system, there are two veins which run along one artery, except of the axillary and subclavian vein (3,5). The number of anatomical variants of the veins of the upper limb seems countless.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation